Bulk mineralogy from February 2019 suspended particulate matter of the St. Lawrence Estuary (eastern Canada) - Anne-Sophie Fabris; Pierre Larouche; Jean-Carlos Montero-Serrano (PANGAEA, 2021)
The mineralogical compositions of ten suspended particulate matter samples taken at a water depth of 10 m along the St. Lawrence Estuary during February 2019 were investigated to document sediment provenance and transport pathways during ice-covered conditions. X-ray diffraction was used for the characterization of the particles extquotesingle mineralogical composition. Samples were analyzed by quantitative X-ray diffraction (qXRD) using a PANalytical X extquotesinglePert Powder diffractometer. For the quantification of the major mineralogical components, the XRD scans obtained were converted into mineral weight percent (wt.%) using the standardless option of the Excel macro-program Rockjock v11.